Platformization of institutional interactions in the context of stimulating innovations in industry - A. I. Shinkevich; F. F. Galimulina (Вестник университета)
The study of theoretical approaches and conceptual analysis helped to clarify the definition of “platformization” from the point of view of network interactions and technological modernization of Russian industry, which formed the basis for the model of institutional interactions platformization, based on the formation of technological alliances that promote innovations, joint value creation by network participants and breakthrough industrial development. On the basis of the dynamic approach, a matrix of positioning of the subjects of the Russian Federation has been constructed, reflecting their distribution in four quadrants, depending on the level and pace of innovative development, and allowing to identify a low share of regions, the regions that demonstrate an intensive increase in innovation activity together with a high rating and a high share of regions that are considered stable weak innovators. The definition of platformization has been formulated in the context of technological development of industry, which distinguishes the use of this category from the “digital” aspect presented in the literature.